National green economy taxonomy - Fayzieva Shodmonovna , Shirin; Sobirova Khaitovna, Markhabo (THE INNOVATION ECONOMY, 2024)
This scientific article analyzes the importance of using economic mechanisms for organizing fruit and vegetable cooperatives in the Republic of Uzbekistan, increasing the volume of fruit and vegetable production, productivity indicators globally and in the country, as well as increasing efficiency. Information on fruits and vegetables in the Kashkadarya region and districts was compared. Based on measures aimed at increasing the efficiency of the food program in our republic, the article reflects the assigned tasks. The analysis also shows that cooperatives make a significant contribution to the regional economy in order to create jobs, develop socio-economic opportunities, and stimulate production growth. In particular, a plan of measures was recommended to ensure the competitiveness of fruits and vegetables grown in agriculture on world markets, which plans to further expand the scope of cooperation with foreign countries in the field of standardization of modern technologies, metrology and quality. Certification, introducing information to exporters about changes in foreign market conditions, promising markets, competitors, reducing the costs of transporting export goods through the development of international transport communications, producing innovative products that are competitive and scientific in all spheres of the economy, reducing transport costs through the introduction of standards, the development of transport and communication systems and the opening of new transport corridors, the introduction of quality control in accordance with the requirements of international standards, strengthening trade, economic and financial cooperation with foreign countries, support for exports from the state - introducing issues of further development of support mechanisms increases the significance of the article.